First record of Prolecithophora (Platyhelminthes) from Argentina: Plagiostomum cilioejaculator sp. n. - Brusa, Francisco (Zootaxa, 2006)
In this work a new benthic species of the genus Plagiostomum is described from the littoral zone of Río de la Plata (Argentina). Plagiostomum cilioejaculator sp. n. is the fourth eyeless species of the genus to be described. The male reproductive system is characterized by a muscular and somewhat curved penis, approximately 260 mm long. The ejaculatory duct is lined by a densely ciliated epithelium. The female reproductive system is typical of the genus. Plagiostomum cilioejaculator sp. n. is the first species of Prolecithophora described from Argentinian waters.